الرقمنة كآلية لتحسين جودة الخدمة العمومية في الجزائر - إبتسام ذرايعية; نجاة صميدة (My University, 2026)
Abstract This study addresses the subject of digitalization as a mechanism for improving the quality of public services in Algeria, highlighting its effective role in advancing administrative performance through the transition from traditional paper-based formats to electronic ones. The study aims to underscore the extent to which digitalization contributes to achieving quality in public services, as well as to identify the key challenges and obstacles facing the digital transformation process in Algeria. To this end, reference was made to several vital sectors implementing digitalization, namely the local government sector (municipalities), the postal sector, and the higher education sector. The study concludes that there is a strong political and legislative will toward adopting and ensuring the success of digitalization, given its significant contribution to improving the quality of public services by accelerating procedures, facilitating service accessibility, and enhancing transparency. However, its practical implementation remains contingent upon the provision of technical and human resources, alongside overcoming various legislative and regulatory barriers. Based on these findings, this study recommends the necessity of upgrading the technological infrastructure, training human resources, and addressing existing legal gaps. These measures are essential to achieving an effective digital transformation that ensures the delivery of public services capable of meeting citizens' expectations. ............................ الملخص تناولت هذه الدراسة موضوع الرقمنة كآلية لتحسين جودة الخدمة العمومية في الجزائر، وذلك لدورها الفعال في الارتقاء بالجانب الإداري، من خلال الانتقال من الشكل التقليدي الورقي إلى الشكل الإلكتروني وتهدف إلى إبراز مدى مساهمة الرقمنة في تحقيق جودة الخدمة العمومية، إضافة إلى التعرف على أهم التحديات والصعوبات التي تواجه عملية التحول الرقمي في الجزائر، لذلك تمت الإشارة إلى بعض القطاعات الحيوية التي تطبق الرقمنة لقطاع الجماعات المحلية (البلدية)، قطاع البريد، قطاع التعليم العالي. وقد خلصت هذه الدراسة إلى وجود إرادة سياسية وتشريعية قوية نحو اعتماد الرقمنة والعمل على إنجاحها، كونها تساهم بشكل كبير في حسين جودة الخدمة العمومية، من خلال تسريع الإجراءات، وتسهيل الوصول إلى الخدمات، وتعزيز الشفافية، إلا أن تجسيدها ميدانيا يبقي مرهونا بتوفير الإمكانيات التقنية والبشرية ، وتجاوز مختلف العراقيل التشريعية والتنظيمية. وتوصي هذه الدراسة بضرورة تحديث البنية التحتية التكنولوجية وتدريب العنصر البشري، واستكمال سد الفجوات القانونية من أجل تحقيق تحول رقمي فعال، يضمن تقديم خدمة عمومية ترقى لتطلعات المواطن. ............................. Résumé Cette étude aborde la numérisation comme levier d'amélioration de la qualité des services publics en Algérie, en soulignant son rôle déterminant dans l'optimisation des performances administratives grâce à la transition des documents papier traditionnels vers les documents électroniques. Elle vise à démontrer la contribution de la numérisation à l'amélioration de la qualité des services publics et à identifier les principaux défis et obstacles rencontrés par le processus de transformation numérique en Algérie. À cette fin, l'étude s'appuie sur l'analyse de plusieurs secteurs clés ayant mis en œuvre la numérisation : les collectivités territoriales, le secteur postal et l'enseignement supérieur. L'étude conclut à une forte volonté politique et législative d'adopter et de garantir le succès de la numérisation, compte tenu de sa contribution significative à l'amélioration de la qualité des services publics : accélération des procédures, facilitation de l'accès aux services et renforcement de la transparence. Toutefois, sa mise en œuvre concrète reste tributaire de la mise à disposition de ressources techniques et humaines adéquates, ainsi que de la levée de divers obstacles législatifs et réglementaires. Au vu de ces constats, l'étude recommande la modernisation de l'infrastructure technologique, la formation des ressources humaines et la résolution des lacunes juridiques existantes. Ces mesures sont essentielles pour parvenir à une transformation numérique efficace qui garantisse la fourniture de services publics répondant aux attentes des citoyens.
Keywords: Keywords: Digitalization; Quality of Public Service; E-Governance; Algeria; الكلمات المفتاحية: الرقمنة ؛ جودة الخدمة العمومية ؛ الإدارة الإلكترونية ؛ الجزائر.; Mots-clés : Numérisation; Qualité du service public; Gouvernance électronique; Algérie